Envelope
041-0157-001 If undelivered return to THE TRADES UNION CONGRESS General Secy: SIR WALTER CITRINE, K.B.E. Transport House, Smith Square, London, S.W.1. Spain Edmonton Labour Party 17 pesetas 13 french francs Mr. Harris, 372 Fore St. Edmonton 292/946/41/157